2002
DOI: 10.1007/s11661-002-0207-1
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation of austenite particles at grain boundaries during aging of Fe-Mn-Ni steel

Abstract: Precipitation of austenite particles at grain and lath boundaries after aging treatment of a Fe-8Mn-7Ni alloy was investigated by selected area electron diffraction (SAD), X-ray energy dispersive spectrometry (EDS) in a scanning transmission electron microscope (STEM), and high-resolution (HRTEM) analysis. High spatial-resolution (2 to 5 nm) EDS analysis revealed no significant segregation of alloying elements at grain boundaries but the precipitation of very fine particles of Mn-and Nirich phase. Detailed EDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…The necessary procedure to differentiate austenite from the -MnNi phase has been documented in our previous work. [21] b. Precipitation of -MnNi intermetallics Figure 6 shows another type of grain-boundary precipitate observed after aging for 30 minutes at 480°C and the diffraction pattern obtained from particle A in Figure 6. These particles are smaller and more numerous than the austenite particles, as can be seen in Figure 4.…”
Section: Diffraction Analysis On Grain-boundary Precipitatesmentioning
confidence: 99%
See 2 more Smart Citations
“…The necessary procedure to differentiate austenite from the -MnNi phase has been documented in our previous work. [21] b. Precipitation of -MnNi intermetallics Figure 6 shows another type of grain-boundary precipitate observed after aging for 30 minutes at 480°C and the diffraction pattern obtained from particle A in Figure 6. These particles are smaller and more numerous than the austenite particles, as can be seen in Figure 4.…”
Section: Diffraction Analysis On Grain-boundary Precipitatesmentioning
confidence: 99%
“…Recent results of high-resolution energy-dispersive spectrometry analysis does not agree with the segregation of the alloying elements at the grain boundaries. [21] An increase in the Mn and Ni peaks in Auger analysis is interpreted as the result of precipitation of fine austenite particles at the grain boundaries. However, embrittlement of the grain boundaries in Fe-Mn-Ni alloys cannot be well explained by the precipitation of fine austenite particles at the grain boundaries.…”
Section: A Embrittlement and De-embrittlement At Grain Boundariesmentioning
confidence: 99%
See 1 more Smart Citation
“…on the grain boundary segregation and brittleness was investigated extensively though they met with little success generally ( . Interestingly, attempts recurred in the last decade using dedicated transmission electron microscopes (TEM) which recognized pronounced grain boundary precipitation reactions in contrast to the earlier reports (Ref [18][19][20]. Moreover, Mn-containing maraging steels have lately drawn considerable attention due to the accelerated clustering of alloying elements in the presence of Mn addition ( Ref 21,22).…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] However, it has recently been found that pronounced grain boundary precipitation causes intergranular brittleness in these steels. For instance, Mun et al [14] reported precipitation of fcc austenite particles at grain boundaries in an Fe-8Mn-7Ni (wt pct) maraging steel. Lee et al [15] then reported precipitation of the fct h-NiMn phase at grain boundaries of an Fe-10Ni-5Mn (wt pct) steel.…”
Section: Introductionmentioning
confidence: 99%